2018
DOI: 10.1111/anu.12816
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of fish oil withSchizochytriummeal and its impacts on the growth and lipid metabolism of Pacific white shrimp (Litopenaeus vannamei)

Abstract: A 12‐week experiment was conducted to evaluate replacing fish oil (FO) in Pacific white shrimp (Litopenaeus vannamei) diets with algal meal (Schizochytrium sp. [AM]) and vegetable oils (VO: linseed oil [L] and soybean oil [S]). For this purpose, 15 aquaria (110‐L each) were arranged in an indoor rack recirculating saltwater system (salinity, 27–28 ppt) and a 2,000‐L mechanical and biological propeller‐washed bead filtration system. Juvenile shrimp (initial weight, 3.15 ± 0.01 g) were randomized into five group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…The current experimental trial to evaluate the effect of diet protein level and the effect of stock strain of freshwater prawn has yielded some interesting findings. A significantly higher hepatopancreatic to osmotic changes was shown in Neohelice granulata (Kumar et al, 2018;Martins et al, 2011). Therefore, gills demonstrate con- suggesting that more conducive water conditions of M. rosenbergii farm were encountered for this experiment than the influence on feed or stock mediated variations.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The current experimental trial to evaluate the effect of diet protein level and the effect of stock strain of freshwater prawn has yielded some interesting findings. A significantly higher hepatopancreatic to osmotic changes was shown in Neohelice granulata (Kumar et al, 2018;Martins et al, 2011). Therefore, gills demonstrate con- suggesting that more conducive water conditions of M. rosenbergii farm were encountered for this experiment than the influence on feed or stock mediated variations.…”
Section: Discussionmentioning
confidence: 68%
“…Fish or shrimp gills are influenced more by osmotic changes than by dietary conditions alone. Change in gills FBPase activity in response to osmotic changes was shown in Neohelice granulata (Kumar et al, ; Martins et al, ). Therefore, gills demonstrate consistent FBPase activity across all experimental groups in this study suggesting that more conducive water conditions of M. rosenbergii farm were encountered for this experiment than the influence on feed or stock mediated variations .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…and other thraustochytrids, as prominent and sustainable sources of oils rich in long‐chain n‐3 polyunsaturated fatty acids (n‐3 LC‐PUFA) and high level of total lipids. Kumar et al () replaced at levels up to three quarters fish oil with Schizochytrium sp. meal, linseed oil and soybean oil in L. vannamei diets.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, dietary fish oil replacement by vegetable oils may change the balance of fatty acid compositions and affect the growth and development of aquatic animals (Li et al, , ; Mu et al, ). Previous studies showed that dietary fish oil replacement with vegetable oils could affect the lipid metabolism of fish, shrimps and crabs (Castro, Corraze, Panserat, & Oliva‐Teles, ; Kumar et al, ; Peng et al, ; Zhao, Long, Wu, Liu, He, et al, ). Meanwhile, dietary fish oil replacement by vegetable oil may also affect the antioxidant capacity and health status of aquatic animals, which could be understood according to the antioxidant indices (Peng, Li, Lin, & Chen, ; Zhang, Li, Liao, Ye, & Wang, ).…”
Section: Introductionmentioning
confidence: 99%